Faktor-Faktor Yang Mempengaruhi Audit Judgment(Studi pada Kantor Akuntan Publik di Kota Surakarta dan Daerah IstimewaYogyakarta) - Wardoyo, Fajar Wisnu, Dra.Mujiyati, M.Si (2016)
The purpose of this study was to determine the effect of gender, obedience pressure, the complexity of the task, and the experience of auditor on audit judgment at the Public Accounting Firm. This study uses empirical studies with surveys. The population in this study were all auditors working in Public Accounting Firm regions Surakarta and Yogyakarta. The sample in this study is partly auditors working in KAP in Surakarta and Yogyakarta. Samples were taken by convenience sampling techniques. Data obtained from questionnaires distributed to a sample. Data were analyzed using classical assumption test and multiple regression analysis. The results showed that obedience pressure and experience influence on audit judgment, whereas gender and the complexity of the task has no effect on audit judgment. Pressure from clients to deviate from professional standards will tend to obey the client orders, so the quality of the audit results will be decline. Auditor experience with can determine the professionalism, commitment to the organization's performance, as well as the quality of auditors through knowledge gained from the experience of conducting the audit